1999
DOI: 10.3133/ofr99255
|View full text |Cite
|
Sign up to set email alerts
|

Basic Requirements for Collecting, Documenting, and Reporting Precipitation and Stormwater-Flow Measurements

Abstract: Knowledge of the characteristics of highway runoff (concentrations and loads of constituents and the physical and chemical processes that produce this runoff) is important for decision makers, planners, and highway engineers to assess and mitigate possible adverse impacts of highway runoff on the Nation's receiving waters. In October, 1996, the Federal Highway Administration and the U.S. Geological Survey began the National Highway Runoff Data and Methodology Synthesis to provide a catalog of the pertinent inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Streamflow discharge, as a volume of water per unit of time passing through a known cross-sectional area, can be measured directly and with low uncertainty by measuring stage at a channel-spanning weir (less than 2% under ideal conditions; Horton [1907], within 5% for calibrated broad-crested weirs; Church et al [1999]) or in-channel flow constriction structures such as a Parshall flumes (about 5% to 8% when considering total measuring uncertainties; Church et al, 1999;Ribeiro et al, 2021). However, these expensive and intensive approaches are typically limited to highlyinstrumented, small, experimental catchments.…”
Section: In-stream Measurementsmentioning
confidence: 99%
“…Streamflow discharge, as a volume of water per unit of time passing through a known cross-sectional area, can be measured directly and with low uncertainty by measuring stage at a channel-spanning weir (less than 2% under ideal conditions; Horton [1907], within 5% for calibrated broad-crested weirs; Church et al [1999]) or in-channel flow constriction structures such as a Parshall flumes (about 5% to 8% when considering total measuring uncertainties; Church et al, 1999;Ribeiro et al, 2021). However, these expensive and intensive approaches are typically limited to highlyinstrumented, small, experimental catchments.…”
Section: In-stream Measurementsmentioning
confidence: 99%
“…freshwater, marine and terrestrial habitats), as part of coordinated and distributed experiments (Fraser et al . ), to simulate and test the impacts of current (Church, Granato & Owens ) or predicted regimes of chemical disturbance. Experiments in terrestrial habitats would be straightforward providing there was sufficient access to electricity and water, and the spatial extent of the plume in soil, air and organisms was quantified to ensure adequate spacing of experimental plots.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring shows organisms in habitats experience complex regimes of chemical disturbance with the concentrations, timing and frequency of toxicants to which these organisms are exposed (e.g. transient contamination events through seasonal urban run‐off; Makepeace, Smith & Stanley ; Church, Granato & Owens ). These regimes are expected to become more complicated due to accelerated chemical production and climatic change (Schiedek et al .…”
Section: Introductionmentioning
confidence: 99%
“…This is less important at larger watersheds best characterized by a network of rain gauges. The basic requirements for collecting, documenting, and reporting precipitation data are summarized in work conducted under the National Highway Runoff Data and Methodology Synthesis (Church, Granato et al 2003).…”
Section: Rainfall Gaugesmentioning
confidence: 99%
“…Among the most important issues cited was a lack of basic information necessary to determine the uncertainty of data sets and documentation of QA/QC practices. This information was considered critical for evaluating the potential utility of available water quality information for any given purpose (Church, Granato et al 2003). They indicated that all studies should provide certain basic data that would eventually lead to the ability of other researchers to independently review the information and make informed decisions as to the utility of the data for other purposes.…”
Section: Reporting and Documentationmentioning
confidence: 99%